PKM Teknik Konseling bagi Dosen Penasehat Akademik FKKH Universitas Nusa Cendana: Pengabdian - Ika Febianti Buntoro; Nicholas Edwin Handoyo; Muntasir, Muntasir; Listyawati Nurina; Halena Meldy Asa; Muhajirin Dean (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
The primary objective of this community service program is to support academic success and improve student well-being through effective mentoring. The training was conducted using an integrated approach. Core activities included the preparation of training materials and media, active listening practice, counseling simulations, workshops on student mental health issues, panel discussions with professional counselors, and the use of questionnaires to identify student needs. Regular monitoring and evaluation of the program were conducted to ensure its effectiveness and continuity. Evaluation results showed a significant increase in the knowledge and practical skills of academic advisors. The average participant knowledge score increased from 60% in the pre-test to 85% in the post-test (a 25-point increase; p < 0.05). Furthermore, practical counseling skills, as measured by simulation observations, increased from 55% to 80%. Student satisfaction surveys with academic and emotional mentoring also saw a 30% increase, with 75% of students reporting feeling more heard and receiving adequate support, up from 45% before the training. The training also strengthened collaboration between instructors and students, with 80% of instructors reporting increased communication frequency and student active participation in mentoring sessions by 40%.